2018
DOI: 10.1186/s12974-018-1163-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the impact of systemic inflammation on neuroinflammation from a non-bacterial endotoxin animal model

Abstract: BackgroundSystemic inflammation induces neuroinflammation and cellular changes such as tau phosphorylation to impair cognitive function, including learning and memory. This study uses a single model, laparotomy without any pathogen, to characterize these changes and their responses to anti-inflammatory treatment in the intermediate term.MethodsIn a two-part experiment, wild-type C57BL/6N mice (male, 3 month old, 25 ± 2 g) were subjected to sevoflurane anesthesia alone or to a laparotomy. Cognitive performance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 41 publications
4
89
0
Order By: Relevance
“…Conversely, the inhibition of COX-2 provides ibuprofen with its analgesic, antipyretic, and anti-inflammatory properties. Research on mice by Huang et al [ 80 ], has demonstrated improved cognitive performance, reduced systemic inflammation and glial activation upon the utilisation of ibuprofen perioperatively. Pre-operative administration of IV ibuprofen has been shown to improve post-operative cognitive function in the clinical setting, where the level of cytokines, cortisol, and catecholamines were reduced [ 81 ].…”
Section: Therapeutic Options For Post-operative Neurological Complicamentioning
confidence: 99%
“…Conversely, the inhibition of COX-2 provides ibuprofen with its analgesic, antipyretic, and anti-inflammatory properties. Research on mice by Huang et al [ 80 ], has demonstrated improved cognitive performance, reduced systemic inflammation and glial activation upon the utilisation of ibuprofen perioperatively. Pre-operative administration of IV ibuprofen has been shown to improve post-operative cognitive function in the clinical setting, where the level of cytokines, cortisol, and catecholamines were reduced [ 81 ].…”
Section: Therapeutic Options For Post-operative Neurological Complicamentioning
confidence: 99%
“…PNDs not only increase the burden on the healthcare system but also lead to postoperative long-term disability and even mortality. The use of volatile anesthetics during surgery has long been suspected of increasing risk of PNDs [ 4 , 5 ]. As the number of surgeries continues to increase, PNDs are expected to become an epidemic [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the number of surgeries continues to increase, PNDs are expected to become an epidemic [ 1 ]. Increasing evidence suggests that PNDs involve neuroinflammation in the hippocampus, at least in their early stages [ 2 , 4 ]. Under certain conditions, secreted chemokines contribute to neuroinflammation in the central nervous system (CNS) [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both systemic inflammation and neuroinflammation, particularly in the hippocampus, triggered by peripheral surgery trauma or anesthesia, have been proposed to be involved in the observed cognitive deficits [21][22][23][24]. Elevated levels of proinflammatory cytokines, such as interleukin-(IL-) 6, IL-1β, and tumor necrosis factor (TNF)-α, have been reported after surgery and may be related to POCD [25]. For instance, Xu et al observed elevated levels of IL-6 following abdominal surgery in the elderly, which positively correlated with decline in cognitive function [26].…”
Section: Attenuation Of Systemic Inflammation Andmentioning
confidence: 99%